Activity antioxidant and sensory profile of jelly candy with addition of butterfly pea (Clitoria ternatea L.) extract powder - HARIADI, Hari; AMIEN, Suseno; DARNIADI, Sandi; SARIFUDIN, Achmat; MAULANA, Haris; DARMAJANA, Doddy Andy; NUGROHO, Pramono; RAHMAT, Ridwan; SUNARMANI, Sunarmani; WIDOWATI, Sri; KARUNIAWAN, Agung; IKRAWAN, Yusep (Food Science and Technology, 2023)
An antioxidant is a compound that can capture free radicals which are active substances that cause various diseases such as cancer. One type of antioxidant is anthocyanin. Anthocyanin pigments in butterfly pea can be used as natural dyes. This study aimed to analyze the anthocyanin content in the manufacturing of jelly candy with butterfly pea extract and preferences that include color, taste, aroma, texture, and acceptability in toddlers. The research design was experimental (posttest only design) with three treatments consisting of the addition of 0.25, 0.50, and 0.75 g of butterfly pea extract. Anthocyanin content was measured using the differential pH method and hedonic organoleptic test. Data were analyzed using the Excel application; if Fh>0.5, then the Duncan test continued. The most liked jelly candy by panelists was the addition of 0.50 g of butterfly pea extract. The nutritional content in 100 g of jelly candy with butterfly pea extract is 289.3 calories, 74.4 g carbohydrates, and 965.75 ppm (965.75 mg/kg) antioxidant activity. The conclusion of the three selected formulations is the addition of 0.50 g.